Undifferentiated small round cell sarcomas in the retroperitoneal space in a 12-year-old female: a rare case report - Liu, Dan; Liu, Xiaoge; Deng, Yan; Wu, Ran; Li, Xin (Frontiers in Pediatrics, 2025)
Undifferentiated small round cell sarcoma (USRCS) is an extremely rare and highly aggressive group of malignant neoplasms affecting bones and soft tissues. USRCSs, particularly extraosseous variants pose significant diagnostic challenges due to their rarity, similar clinicoradiological features, nonspecific morphology and the necessity for comprehensive molecular analyses. This paper discusses a rare interesting case of retroperitoneal USRCS in a 12-year-old female with a five-day history of diarrhea and slight right lower abdominal pain. Hematological profile, renal function test, liver function test and tumor markers were in normal limits. Preoperative imaging revealed a well-defined, highly vascularized mass in the lower right retroperitoneal space, featuring patchy calcification and osseous and fatty components that compressed the right ureter, causing obstructive hydroureteronephrosis. Given the clinical and imaging findings. The lesion was initially misdiagnosed as a benign teratoma. However, postoperative pathology and genetic testing confirmed USRCS, remarkably, the Ki-67 index was only 10%. The patient did not undergo any additional postoperative treatment and achieved long-term survival. Despite USRCS in the retroperitoneal space with calcification has been reported, we believe this is the first published case of USRCS with calcification and osseous and fatty components mimicking teratoma. The case is important in that it demonstrates the unusual imaging appearance of retroperitoneal USRCS.